2011
DOI: 10.1097/mej.0b013e3283462504
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology surveillance system of the Spanish Society of Paediatric Emergencies

Abstract: We aim to describe the characteristics and the management of the paediatric poisonings registered in the Toxicology Surveillance System created by the Intoxications Working Group of the Spanish Society of Paediatric Emergencies. We reviewed 130 episodes registered during 1 year. The main involved substances were drugs (73, 56.2%), household products (24,18.5%) and ethanol (16, 12.3%). Most common mechanisms were accidental poisonings at home in children of less than 5 years (91, 70%; principally, paracetamol o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 0 publications
4
18
1
3
Order By: Relevance
“…In the group of children studied who were hospitalised at the HED, it was also found that self-harm occurred most frequently in 13–15-year-old girls hospitalised due to intentional drug poisoning. Similar tendencies were observed in children hospitalised in Spain11 and in Turkey, in adult women poisoned by drugs 16…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the group of children studied who were hospitalised at the HED, it was also found that self-harm occurred most frequently in 13–15-year-old girls hospitalised due to intentional drug poisoning. Similar tendencies were observed in children hospitalised in Spain11 and in Turkey, in adult women poisoned by drugs 16…”
Section: Discussionsupporting
confidence: 70%
“…These data are difficult to compare with studies conducted by other authors, as the poisonous substances were classified differently in each case. Worth noting is the fact, however, that drug poisonings were considerably less frequent in our region than in such countries—for example, Spain,6 11 Israel,15 Turkey,16 or Pakistan,5 where they represented 50% of all poisonings, with alcohol occupying a more distant position 6 11 16. One of the reasons may be related to religion, namely Islam, and the resulting alcohol prohibition, although in Iran,10 where drinking alcohol is illegal, it is the leading cause of poisoning hospitalisations.…”
Section: Discussionmentioning
confidence: 71%
“…This has led to the establishment of several mechanisms for population surveillance outside the US, such as the Alerting and Surveillance Using Poisons Information Systems [11] as well as other medical informatics platforms [12]. Recent attempts to explore patterns and magnitude of consequential pediatric poisonings have also been made outside North America: the Spanish Society of Paediatric Emergencies reported 91 poisonings in children younger than 5 years over 1 year through their Toxicology Surveillance System-Intoxications Working Group [13]. Of the 91 cases, 70 % were exposed to acetaminophen or cough and cold medications.…”
Section: Discussionmentioning
confidence: 99%
“…Estos estudios son probablemente dispares en cuanto a instrumentos y méto-dos de recogida de datos y carecen de representatividad estatal, pero pueden ayudar a hacerse una idea del peso y las característi-cas de las IEA. Se estima que entre 1998 y 2010 en los servicios hospitalarios españo-les de urgencias las IEA supusieron aproximadamente un 0,5-1,1% del conjunto de urgencias atendidas, el 25-49% del total de intoxicaciones por cualquier sustancia y el 45-65% del total de intoxicaciones por drogas de abuso [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94] . El peso del problema en las urgencias extrahospitalarias era seguramente incluso mayor 84 .…”
Section: Intoxicación Etílica Aguda (Iea)unclassified